Motility in blastogregarines (Apicomplexa): Native and drug-induced organisation of Siedleckia nematoides cytoskeletal elements. - Andrea Valigurová; Naděžda Vaškovicová; Andrei Diakin; Gita G Paskerova; Timur G Simdyanov; Magdaléna Kováčiková (PLoS ONE)
Recent studies on motility of Apicomplexa concur with the so-called glideosome concept applied for apicomplexan zoites, describing a unique mechanism of substrate-dependent gliding motility facilitated by a conserved form of actomyosin motor and subpellicular microtubules. In contrast, the gregarines and blastogregarines exhibit different modes and mechanisms of motility, correlating with diverse modifications of their cortex. This study focuses on the motility and cytoskeleton of the blastogregarine Siedleckia nematoides Caullery et Mesnil, 1898 parasitising the polychaete Scoloplos cf. armiger (Müller, 1776). The blastogregarine moves independently on a solid substrate without any signs of gliding motility; the motility in a liquid environment (in both the attached and detached forms) rather resembles a sequence of pendular, twisting, undulation, and sometimes spasmodic movements. Despite the presence of key glideosome components such as pellicle consisting of the plasma membrane and the inner membrane complex, actin, myosin, subpellicular microtubules, micronemes and glycocalyx layer, the motility mechanism of S. nematoides differs from the glideosome machinery. Nevertheless, experimental assays using cytoskeletal probes proved that the polymerised forms of actin and tubulin play an essential role in the S. nematoides movement. Similar to Selenidium archigregarines, the subpellicular microtubules organised in several layers seem to be the leading motor structures in blastogregarine motility. The majority of the detected actin was stabilised in a polymerised form and appeared to be located beneath the inner membrane complex. The experimental data suggest the subpellicular microtubules to be associated with filamentous structures (= cross-linking protein complexes), presumably of actin nature.